Peran Kepala Madrasah Sebagai Motivator dan Inovator Peningkatan Mutu Lembaga - Munardji Munardji (Institut Agama Islam Negeri (IAIN) Tulungagung, 2014)
Improving the quality of education is closely related to improving human resource. Meanwhile, the quality of human resources at school is a partly relied to the quality of the principal. A principal is responsible to the success or failure of education. The problem lies upon the difficulty to find a credible principal who can manage the institution quite well. The jobs of a principal are (1) encourage the teachers to have continuous professional development, (2) become role model for everybody at school, (3) make innovation for the institution.